Random Video Call and Chat Application Using Web RTC and Firebase Based on Mobile - Tengku Luthfi Davyan; Leni Marlina; Abdul Khaliq (Yayasan Sinergi Multidimensi Kreatif, 2024)
Humans as social beings, require communication and interaction. Communication technology found in smartphones plays a crucial role in accelerating access to social media. However, traditional social media often only provides written and asynchronous communication, which can reduce the motivation to participate. This research aims to develop a mobile application that integrates video call and random chat features using WebRTC and Firebase technology. The research method includes developing the application using React Native as the framework, Firebase for real-time database management and authentication, and WebRTC for handling real-time video communication. The research results show that the developed application can provide optimal performance in terms of latency and video call quality, as well as functional login, registration, chat, and video call features. This application opens the door to more direct, interactive, and natural human engagement by offering a more spontaneous and unpredictable meeting experience. The conclusion of this research is that integrating WebRTC and Firebase in the development of video call and random chat applications can provide an efficient and enjoyable communication experience for users.Application